The short-term effect of air pollution on the incidence of pulmonary tuberculosis in Chongqing, China, 2014-2020 - Deng, Xinyi; Xing, Dianguo; Chen, Zhiyi; Zou, Yang; He, Ying; Chen, Saijuan; Wang, Qiuting; Zhang, Yan (The Journal of Infection in Developing Countries, 2023)
Introduction: Tuberculosis (TB) is one of the top ten causes of death in the world. The purpose of this study was to explore the relationship between the short-term exposure to air pollutants and the risk of pulmonary TB in Chongqing. Methodology: A distributed lag nonlinear model was used to explore the effect of short-term exposure to air pollutants on the risk of pulmonary TB. Stratified analysis was used to explore the impact of gender and age on the risk of pulmonary TB. Results: There were 170,934 confirmed cases of pulmonary TB in Chongqing from January 1st, 2014 to December 30th, 2020. There was a positive correlation between the exposure to particulate matter with aerodynamic diameter less than 2.5 µm (PM2.5), particulate matter with aerodynamic diameter less than 10 µm (PM10) ozone (O3) and the incidence risk of TB. The maximum lag-specific relative risk (RR) of pulmonary TB was 1.012 (95% CI: 1.001-1.023, 14 days delay) for each 10 μg/m3 increase in PM2.5; 1.010 (95% CI: 1.003-1.017, 14 days delay) for each 10μg/m3 increase in PM10; and 1.002 (95% CI:1.000-1.004, 2 days delay) for each 10 mg/m3 increase in O3. Stratified analysis showed that the exposure effects of PM2.5, PM10 and O3 were different between different genders and age. Conclusions: This study suggested that exposure to PM2.5, PM10, and O3 was associated with the risk of pulmonary TB, and the risk was higher for males than females, while the exposure to PM2.5 and PM10 was riskier for people aged 15-60 years.